Expectation of individual packet transmission times in reliable broadcast - Kai-yun WANG; You-ping LI; Si-qi KONG; Qiang1 ZHAO; Wei-dong MA (Tongxin xuebao)
In one-many transmission model, broadcast/multicast was more effective than unicast at delivery efficiency. The mathematical expectation of individual packet transmission times was a fundamental parameter in the theory of reli-able broadcast. Up to now, there were two categories of solutions for this parameter in relevant literatures: exact series solutions and approximate solutions used for analyzing complexities. The former may consume too much computing time, and the latter's precision was very low in some regions. Combining one series solution with the solution based on the as-sumption of continuous probability distribution, derive a few simple and high-precision solutions whose physical mean-ings were more obvious. Simulation shows that the average deviation has been lower than the current solution 2～3 order of magnitude.